PETER BIRKS AND COMPARATIVE LAW - Smith, Lionel (Revue de droit de l'Université de Sherbrooke, 2013)
This paper studies aspects of the thought of Peter Birks in relation to comparative law, Roman law, legal scholarship and legal education. Birks valued comparative law, and thought that it could be more thoroughly integrated into research and teaching in law. About Roman law, however, he was passionate. He viewed it as a fascinating object of study and reflection, and as an essential part of undergraduate legal education. He deprecated the decline of Roman law as part of the law school curriculum. In this paper, I suggest that one reaction to the decline of Roman law in legal education could be a more comprehensive embrace of comparative law. If comparative law were integrated carefully into the curriculum, it could bring to students all of the benefits that Birks found in the study of Roman law.